Pyrosequencing evaluation of low-frequency KRAS mutant alleles for EGF receptor therapy selection in metastatic colorectal carcinoma. (April 2014) - Natalicchio, Maria Iole; Improta, Giuseppina; Zupa, Angela; Cursio, Olga Elisabetta; Stampone, Emanuela; Possidente, Luciana; Teresa Gerardi, Assunta Maria; Vita, Giulia; Martini, Maurizio; Cassano, Alessandra; Piccoli, Claudia; Romito, Sante; et al.
ABSTRACT: : Aim: To evaluate whether pyrosequencing (PS) improves the KRAS mutational status predictive value.Patients & methods: A retrospective analysis of KRAS mutations by PS and direct sequencing (DS) in 192 metastatic colorectal carcinomas (mCRCs), subgrouped in 51 KRAS mutated at PS and 141 KRAS wild-type at DS.Results: DS failed to detect low-frequency KRAS mutations in four out of 51 mCRCs, whereas PS detected 12 additional low-frequency KRAS mutations in 141 mCRCs KRAS wild-type at DS. After reanalyzing by PS 97 KRAS wild-type tumors treated with anti-EGF receptor (EGFR) antibodies, nine additional mutations were revealed in nonresponders, whereas none of responders exhibited a KRAS -mutated genotype. Of note, KRAS -mutated tumors upon PS showed a worst progression-free survival after EGFR therapy. Finally, PS allowed the detection of additional NRAS, BRAF and exon 20 PIK3CA mutations mostly in KRAS wild-type mCRCs resistant to EGFR therapy.Conclusion: PS detection of low-frequency mutations may improve the KRAS predictive value for EGFR therapy selection.